Strategi Prioritas dalam Mengembangkan Lidi Sawit di Kabupaten Bengkalis - Sutrisno, Sutrisno; Hendri, Zul (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to formulate strategic priorities for developing palm stick (lidi sawit) as a local economic commodity in Bengkalis Regency, which remains underutilized despite its potential. The main challenges include limited technological support, restricted market access, insufficient funding, and weak collaboration among stakeholders. A quantitative approach was applied using the Analytic Network Process (ANP) to analyze the interrelationships and priority weights among strategic elements in a holistic manner. Data were collected through in-depth interviews and expert questionnaires involving local industry actors. The results indicate that the top strategic priority is strengthening business institutions and local government regulatory support, followed by enhancing market access and processing technology. These findings suggest that palm stick development requires an integrated approach through multi-sector collaboration and policies grounded in local potential. The study recommends the formulation of a sustainable development roadmap for palm sticks to optimize their contribution to regional economic growth.